Enhancement of acaricide activity of citronella oil after microemulsion preparation - Wasana Chaisri (2019)
© 2019, Hokkaido University. All rights reserved. Enhancement of acaricide activity of citronella oil after microemulsion preparation Abstract The objectives of this study were to evaluate the preparation of microemulsions for citronella oil and subsequently to compare their acaricide efficacy as against conventional citronella oil. The chemical analysis of the commercial citronella oil used was carried out using an Agilent 6890 gas chromatograph (GC) coupled to an electron impact ionization (EI, 70 eV) with an HP 5973 mass selective detector (MSD). In comparison among the emulsifier systems, the mixture of Tween 20 with propylene glycol in ratios 3: 1, 2: 1, 1: 1, 1: 2, and 1: 3, the pseudoternary phase diagrams were conducted and used to define the most suitable system for preparing citronella oil microemulsions and using them in acaricide efficacy testing. The citronella microemulsions in concentrations ranging from 0.39-25% w/w were prepared and tested for their acaricide efficacies using Adult Immersion Test and Larval Package Test. The acaricide efficacies were determined by percentages of mortalities of larval and adult ticks and the values of LC50 and LC99. Results show that the most suitable emulsifier system was in a ratio of 3: 1. The physicochemical characteristics indicated that the size of the microemulsions were in the range of 19.6 ± 0.4 nm to 47.3 ± 2.3 nm with moderate polydispersity index (0.3-0.7). The microemulsions had stronger acaricide efficacy than the conventional citronella oil, indicated by significant lower LC50 and LC99 values. The LC99 of the microemulsions against larval and adult ticks at 24 h were 0.78% w/w (0.56-1.02) and 28.4% w/w (23.27-37.43), respectively. These results demonstrated that microemulsion preparation can be used to improve the acaricide efficacy of citronella oil.